2022
DOI: 10.1177/03635465221125780
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the Tibial Tubercle–Trochlear Groove Distance: Evaluation of Rotational Factors, Trochlear Groove and Tibial Tubercle Position, and Role of Trochlear Dysplasia

Abstract: Background: The tibial tubercle to trochlear groove (TT-TG) distance is often utilized for determining the surgical treatment for patients with patellar instability (PI). It is thought to directly represent the position of the TT on the tibia. Recent work has shown that the measurement of the TT-TG distance is multifactorial. Purpose: To investigate the relationship between relative tibial external rotation (rTER) and trochlear dysplasia (TD), as well as the location of the TG and TT in patients with and witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Meanwhile, the systematic review by Ren et al compared outcomes following isolated trochleoplasty (three studies, n = 111 patients) versus trochleoplasty + MPFL reconstruction (three studies, n = 81 patients) [30]. At the final follow‐up, Kujala score was found to increase significantly ( p < 0.00001) in both the isolated trochleoplasty group (21.4 points, mean follow‐up 39 months) and trochleoplasty + MPFL reconstruction group (24.9 points, mean follow‐up 29.8 months) [26]. Similarly, Guan‐Yan et al analysed 17 studies comparing trochleoplasty to other patellar stabilising procedures (MPFL reconstruction, medial retinaculum repair and Insall proximal realignment) in the setting of severe trochlear dysplasia [33].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the systematic review by Ren et al compared outcomes following isolated trochleoplasty (three studies, n = 111 patients) versus trochleoplasty + MPFL reconstruction (three studies, n = 81 patients) [30]. At the final follow‐up, Kujala score was found to increase significantly ( p < 0.00001) in both the isolated trochleoplasty group (21.4 points, mean follow‐up 39 months) and trochleoplasty + MPFL reconstruction group (24.9 points, mean follow‐up 29.8 months) [26]. Similarly, Guan‐Yan et al analysed 17 studies comparing trochleoplasty to other patellar stabilising procedures (MPFL reconstruction, medial retinaculum repair and Insall proximal realignment) in the setting of severe trochlear dysplasia [33].…”
Section: Discussionmentioning
confidence: 99%
“…3,27 We assessed the TT-TG distance using the most distal and proximal axial slice displaying full cartilage coverage of the trochlear groove and the most proximal slice of the patellar tendon insertion on the tibial tuberosity. 28,31 The TT-TG was defined as the distance between the midpoint of the tibial insertion of the patellar tendon and the deepest point of the trochlear groove when measured parallel to the tangent along the posterior femoral condyles (posterior condylar axis).…”
Section: Mri Measurementsmentioning
confidence: 99%
“…The TT–TG distance is a widely used parameter to evaluate the lateral offset of the distal extensor mechanism, which is of importance given that it represents a risk factor for RPD and is often included in algorithmic treatment of RPD [5]. Recently, many researchers have turned their attention towards the underlying causes of increased TT–TG distance [3, 20, 26, 27, 29]. Interestingly, some radiologic studies have found that TT–TG distance is more affected by tibiofemoral rotation (TFR) than by actual tibial tubercle lateralisation (TTL) [26, 29], suggesting that the impact of actual TTL on the TT–TG distance is less important than previously thought.…”
Section: Introductionmentioning
confidence: 99%